2007
DOI: 10.1111/j.1399-3046.2006.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cyp3a5 genotype on tacrolimus pharmacokinetics and pharmacodynamics in young kidney transplant recipients

Abstract: CYP3A enzyme plays a pivotal role in TAC metabolism. The aim of this study was to analyze retrospectively the influence of CYP3A5 gene polymorphism on TAC pharmacokinetics and pharmacodynamics in 30 teenage kidney transplant recipients. TAC dose, trough blood levels, apparent volume of distribution, as well as blood pressure and antihypertensive therapy obtained at different post-transplant periods, were correlated with the corresponding genotype. Despite a therapeutic monitoring strategy, heterozygotes (CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 20 publications
13
34
0
1
Order By: Relevance
“…[17] Other investigators have also reported that CYP3A5 expressers do not have a higher risk of developing acute rejection. [18][19][20][21][22][23][24][25][26] Although numerous studies have reported the higher Tac dose requirement of CYP3A5 expressers compared to nonexpressers, the clinical relevance of this association is unclear and has so far only been investigated in two randomized-controlled clinical trials (RCT). The Tactique study [27] was a multicenter RCT, including 280 renal transplant recipients.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…[17] Other investigators have also reported that CYP3A5 expressers do not have a higher risk of developing acute rejection. [18][19][20][21][22][23][24][25][26] Although numerous studies have reported the higher Tac dose requirement of CYP3A5 expressers compared to nonexpressers, the clinical relevance of this association is unclear and has so far only been investigated in two randomized-controlled clinical trials (RCT). The Tactique study [27] was a multicenter RCT, including 280 renal transplant recipients.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…Individuals expressing CYP3A5 may have higher clearance and lower bioavailability of CYP3A substrates compared with individuals not expressing CYP3A5 (Kuehl et al, 2001). This has been demonstrated for both the immunosuppressive drug tacrolimus and for several HMG-CoA reductase inhibitors (statins) where patients expressing CYP3A5 need higher drug dosages to reach target serum concentration or to achieve sufficient lipid-lowering response, respectively (Hesselink et al, 2003;Zheng et al, 2003;Goto et al, 2004; Kivisto et al, 2004;Ferraresso et al, 2007). CYP3A4 and CYP3A5 overlap in substrate specificity, but the relative importance of CYP3A4 and CYP3A5 in overall CYP3A-mediated metabolism differs between substrates .…”
mentioning
confidence: 99%
“…CYP3A5*1 allele carriers ("high expressors") are known to require larger doses of tacrolimus to reach target blood concentrations than homozygous carriers of the CYP3A5*3 allele ("low expressors"). [3][4][5][6] In addition, CYP3A5 "high expressors" may require a longer period (up to 2 weeks) to achieve target blood concentrations than CYP3A5 "low expressors". 4 Macphee and others 4 reported lower tacrolimus concentrations in CYP3A5 "high expressors" during the first 2 weeks after renal transplant, despite therapeutic drug monitoring, and a significant delay in the time to reach target tacrolimus concentrations relative to CYP3A5 "low expressors".…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Previous studies have shown that carriers of the CYP3A5*1 allele require larger doses of tacrolimus to achieve target blood concentrations than patients with other alleles. [3][4][5][6] The frequency of this allele varies depending on ethnicity and is more common among Asian and African American people than among whites. 7 Rifampin is known to affect the metabolism of tacrolimus through induction of CYP3A4 8 and, to a far lesser extent, CYP3A5.…”
Section: Introductionmentioning
confidence: 99%